2014
DOI: 10.1016/j.jct.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of micellisation: Sodium dodecyl sulfate/sodium deoxycholate with polyethylene glycol and model drugs

Abstract: Variations in the critical micelle concentration (CMC) have been determined for sodium dodecyl sulfate and sodium deoxycholate (NaDC) in the presence of five drugs and polyethylene glycol (PEG) at 298.2, 304.2 and 310.2 K. From these data, thermodynamic parameters associated with the micellisation process (∆G mic , ∆H mic and ∆S mic ) were calculated. In the presence of some drug-based compounds the CMC of SDS was affected, for example the presence of PEG dramatically reduced the CMC in all cases. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous work from our group and other researchers has confirmed that isothermal titration calorimetry (ITC) is an appropriate analytical technique to determine the binding interaction of several drug-based systems, such as those based on micelles, 10,11 cyclodextrins, [12][13][14] and polymer aggregates. 15 More recently, polymer beads have been studied using one drug, namely doxorubicin, with one bead type, namely DC BeadM1™ (a sulfonate-modified polyvinylalcohol hydrogel bead termed PVA-AMPS), and found the drug to binding sites on the bead ratio to be far lower than anticipated when compared with previously established binding data.…”
Section: Introductionmentioning
confidence: 98%
“…Previous work from our group and other researchers has confirmed that isothermal titration calorimetry (ITC) is an appropriate analytical technique to determine the binding interaction of several drug-based systems, such as those based on micelles, 10,11 cyclodextrins, [12][13][14] and polymer aggregates. 15 More recently, polymer beads have been studied using one drug, namely doxorubicin, with one bead type, namely DC BeadM1™ (a sulfonate-modified polyvinylalcohol hydrogel bead termed PVA-AMPS), and found the drug to binding sites on the bead ratio to be far lower than anticipated when compared with previously established binding data.…”
Section: Introductionmentioning
confidence: 98%